Genome-wide identification and comprehensive characterization of the ADF gene family in Triticum monococcum L. subsp. aegilopoides with insights into structure, evolution and cold stress response - Liu, Xin; Zhang, Minghu; Su, Jian; Wu, Lei; Shen, Mang; Wang, Qi; Zhuang, Yamei; Zhang, Lianquan; Li, Haosheng; Chen, Gang (Frontiers in Plant Science, 2025)
Actin-depolymerizing factors (ADFs) play crucial roles in cytoskeletal dynamics and stress adaptation in plants. In this study, we identified nine ADF genes (TbADF1 to TbADF9) in Triticum monococcum L. subsp. aegilopoides. Chromosomal distribution analysis revealed that these genes are unevenly distributed across five chromosomes, with evidence of tandem duplication events. Phylogenetic analysis clustered the TbADFs into four subfamilies, indicating evolutionary conservation among wheat relatives. Gene structure and motif analyses confirmed the presence of a conserved ADF domain. Additionally, promoter region analysis revealed a variety of cis-regulatory elements associated with hormone signaling and stress responses. Predictions of binding pockets and protein–protein interaction networks indicated potential functional sites and interactions with cytoskeletal regulators. Codon usage bias analysis showed a preference for GC-rich codons, which may enhance translation efficiency under stress. Codon usage bias analysis indicated GC-rich optimization, potentially enhancing translation efficiency under stress. Promoter methylation levels ranged from 0.0907 to 0.3053, suggesting that epigenetic regulation may contribute to the control of gene expression. Transcriptomic profiling across six tissues and under cold stress conditions (4°C for 24 hours) revealed both tissue-specific expression patterns and differential cold responses. Notably, TbADF1, TbADF4, TbADF6, and TbADF7 were upregulated, with TbADF6 exhibiting the strongest induction, as its TPM value increased from 29.07 to 300.01. Furthermore, co-expression and gene ontology enrichment analyses of the upregulated genes identified key biological pathways involved in membrane integrity, phosphorylation, ribosome maturation, and lipid signaling. These findings highlight the central role of TbADF6 in cold adaptation.